Composition, lubricating oil composition, and grease composition

A composition with metal nanoparticles and a specific vinyl polymer improves dispersibility in lubricating oils and greases, addressing the dispersibility issues at high temperatures and in grease environments.

CN119137248APending Publication Date: 2024-12-13IDEMITSU KOSAN CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380031460.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-31
Filing Date
2023-03-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing lubricating oil and grease compositions with metal nanoparticles suffer from insufficient dispersibility at high temperatures and in grease environments.

Method used

A composition comprising metal nanoparticles, a vinyl polymer with a chain alkyl group and nitrogen-containing heterocyclic group, and a dispersion medium, which enhances dispersibility in lubricating oils and greases.

Benefits of technology

The composition provides improved dispersibility of metal nanoparticles in high-temperature environments and greases, enhancing the performance of lubricating oils and greases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005064620440000091
    Figure BDA0005064620440000091
  • Figure BDA0005064620440000101
    Figure BDA0005064620440000101
  • Figure BDA0005064620440000301
    Figure BDA0005064620440000301
Patent Text Reader

Abstract

A composition containing metal nanoparticles (X), a polymer (Y), and a dispersion medium, the polymer (Y) being a vinyl polymer having a C10-28 chain alkyl group and a nitrogen-containing heterocyclic group, the metal nanoparticles (X) and the polymer (Y) being dispersed in the dispersion medium, the composition is useful as an additive composition for a lubricating oil composition, an additive composition for a grease composition, a lubricating oil composition or a grease composition. The polymer (Y) is one or more types selected from the group consisting of a polymer (Y1) and a polymer (Y2), and the polymer (Y1) contains two or more types selected from the group consisting of a constituent unit derived from the following monomer (ya), a constituent unit derived from the following monomer (yb), and a constituent unit derived from the following monomer (yc). And a polymer (Y2) that contains a constituent unit derived from the following monomer (yb) and does not contain a constituent unit derived from the following monomer (ya) and a constituent unit derived from the following monomer (yc). Monomer (ya): C12-30 olefin monomer (y): vinyl monomer having a nitrogen-containing heterocyclic group in which at least one hydrogen atom is substituted by a C12-30 chain alkyl group. Monomer (y): vinyl monomer having a nitrogen-containing heterocyclic group in which all hydrogen atoms are not substituted by a C12-30 chain alkyl group.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to compositions, lubricating oil compositions, and lubricating grease compositions. Background Art

[0002] Metallic particles dispersed in a lubricating base oil have the potential to impart various functions to the lubricating base oil. Therefore, various studies have been conducted on lubricating oil compositions in which metallic particles are blended in a lubricating base oil.

[0003] In recent years, research has been conducted on lubricating oil compositions in which metal nanoparticles, which are extremely fine metal particles, are blended into lubricating oil base oils. For example, Patent Documents 1 and 2 describe that by adding metal nanoparticles and acrylate polymers in combination to lubricating oil base oils, the metal nanoparticles can be dispersed very well in the lubricating oil base oil, and a lubricating oil composition having improved extreme pressure performance and friction reduction performance can be provided.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application No. 2021-512188

[0007] Patent Document 2: Japanese Patent Application No. 2021-512189 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, the technologies described in Patent Documents 1 and 2 do not have sufficient dispersibility of metal nanoparticles in a high temperature environment (e.g., 200° C. or higher) that is assumed in the use of the lubricating oil composition. In addition, the technologies described in Patent Documents 1 and 2 do not have sufficient dispersibility of metal nanoparticles in the grease.

[0010] Therefore, an object of the present invention is to provide a composition, a lubricating oil composition, and a grease composition in which the dispersibility of metal-based nanoparticles is improved.

[0011] Solutions to Solve Problems

[0012] According to the present invention, the following [1] to [4] can be provided.

[0013] [1] A composition comprising metal nanoparticles (X), a polymer (Y) and a dispersion medium,

[0014] The polymer (Y) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group,

[0015] The metal nanoparticles (X) and the polymer (Y) are dispersed in a dispersion medium,

[0016] The composition is used as an additive composition for a lubricating oil composition, an additive composition for a grease composition, a lubricating oil composition or a grease composition.

[0017] [2] A method for producing a composition, comprising the following step (1):

[0018] Step (1): a step of dispersing a precursor of metal nanoparticles (X) in the presence of a polymer (Y) and a dispersion medium,

[0019] The polymer (Y) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group.

[0020] [3] A lubricating oil composition comprising metal nanoparticles (X), a polymer (Y) and a lubricating oil base oil,

[0021] The polymer (Y) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group,

[0022] The metal nanoparticles (X) and the polymer (Y) are dispersed in a lubricating base oil.

[0023] [4] A grease composition comprising metal nanoparticles (X), a polymer (Y) and a grease,

[0024] The polymer (Y) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group,

[0025] The metal nanoparticles (X) and the polymer (Y) are dispersed in the grease.

[0026] Effects of the Invention

[0027] According to the present invention, there can be provided a composition, a lubricating oil composition, and a grease composition having improved dispersibility of metal-based nanoparticles. DETAILED DESCRIPTION

[0028] The upper limit and lower limit of the numerical range described in this specification can be arbitrarily combined. For example, when "A to B" and "C to D" are described as numerical ranges, the numerical ranges of "A to D" and "C to B" are also included in the scope of the present invention.

[0029] In addition, the numerical range "lower limit value to upper limit value" described in this specification means more than the lower limit value and less than the upper limit value unless otherwise specified.

[0030] In addition, in this specification, the numerical values ​​of Examples are numerical values ​​that can be used as upper limits or lower limits.

[0031] [Form of composition]

[0032] The composition of the present embodiment contains metal nanoparticles (X), a polymer (Y), and a dispersion medium.

[0033] The polymer (Y) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group.

[0034] Furthermore, in the composition of this embodiment, the metal nanoparticles (X) and the polymer (Y) are dispersed in a dispersion medium and used as an additive composition for a lubricating oil composition, an additive composition for a grease composition, a lubricating oil composition or a grease composition.

[0035] The present inventors have conducted intensive studies to solve the above problems and have found that the composition having the above structure is extremely excellent in the dispersibility of metal nanoparticles.

[0036] When describing in more detail, it was found that for the composition having the above-mentioned structure, the dispersibility of the metal nanoparticles is excellent even in a high temperature environment (for example, above 200°C) assumed in the use of the lubricating oil composition, and the dispersibility of the metal nanoparticles is also excellent in the grease composition.

[0037] Although the details of the mechanism by which the effects of the present invention are exerted are not yet clear, it is presumed that the structure of the polymer (Y) used in the present embodiment contributes to the improvement of the dispersibility of the metal nanoparticles.

[0038] Hereinafter, the “metal nanoparticles (X)”, “polymer (Y)”, and “dispersion medium” constituting the composition of the present embodiment will be described in detail.

[0039] <Metallic Nanoparticles (X)>

[0040] The composition of this embodiment contains metal nanoparticles (X).

[0041] In the present embodiment, the metal nanoparticles (X) are particles having an average particle diameter of the order of nm (nanometers), that is, smaller than 1 μm.

[0042] Here, from the viewpoint of improving dispersibility, the average particle diameter of the metal nanoparticles (X) is preferably below 800nm, more preferably below 600nm, further preferably below 500nm, further preferably below 400nm, further more preferably below 300nm, and more preferably below 200nm. In addition, the average particle diameter of the metal nanoparticles (X) is usually more than 10nm.

[0043] It should be noted that the "average particle size of the metal nanoparticles (X)" in this embodiment refers to the average particle size at 25°C in a state dispersed in a dispersion medium, obtained by implementing the measurement method in "1. Study on dispersibility of metal nanoparticles" of the examples described later.

[0044] In the present specification, the “average particle size” refers to the particle size of the integrated value Z-avarage in the particle size distribution determined by a dynamic light scattering method.

[0045] In addition, in this embodiment, "metal-based" is not limited to metals, and is a concept including metal oxides, metal nitrides, metal sulfides, metal carbides, metal borides, and the like.

[0046] However, boron is excluded from the metal elements constituting the metal boride.

[0047] In this embodiment, from the viewpoint of improving dispersibility, etc., the metal-based nanoparticles (X) preferably include metal-based nanoparticles (X1), wherein the metal-based nanoparticles (X1) are metal nanoparticles formed from one or more metal elements (x1) selected from transition metal elements and metal elements and semi-metal elements of Groups 12 to 15, nanoparticles formed from oxides of the metal element (x1), nanoparticles formed from nitrides of the metal element (x1), nanoparticles formed from sulfides of the metal element (x1), nanoparticles formed from carbides of the metal element (x1), and one or more metal-based nanoparticles formed from borides of the metal element (x1).

[0048] The content of the metal nanoparticles (X1) in the metal nanoparticles (X) is preferably 50% to 100% by mass, more preferably 60% to 100% by mass, further preferably 70% to 100% by mass, further preferably 80% to 100% by mass, and further more preferably 90% to 100% by mass, based on the total amount of the metal nanoparticles (X), from the viewpoint of improving dispersibility.

[0049] The metal element (x1) is specifically exemplified below.

[0050] As the transition metal elements, there can be mentioned scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni) and copper (Cu) as the first transition metal element; yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), palladium (Pd), and silver (Ag) as the second transition metal element; The three transition metal elements are lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Em), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), Ho (holmium), Er (erbium), thulium (Tm), ytterbium (Yb), lutetium (Lu), hafnium (Hf), tantalum (Ta), tungsten (W), rhenium (Re), osmium (Os), iridium (Ir), platinum (Pt), and gold (Au).

[0051] As metal elements of Groups 12 to 15, zinc (Zn), cadmium (Cd), and mercury (Hg) as metal elements of Group 12; aluminum (A1), gallium (Ga), indium (In), and thallium (T1) as metal elements of Group 13; germanium (Ge), tin (Sn), and lead (Pb) as metal elements of Group 14; and bismuth (Bi) as metal element of Group 15.

[0052] Examples of the semi-metallic elements of Groups 12 to 15 include boron (B), silicon (Si), germanium (Ge), arsenic (As), antimony (Sb), and tellurium (Te).

[0053] Among the above-mentioned metal elements (x1), from the viewpoint of availability and economy, it is preferably one or more selected from titanium (Ti), manganese (Mn), iron (Fe), nickel (Ni), copper (Cu), zirconium (Zr), molybdenum (Mo), tungsten (W), zinc (Zn), boron (B), and aluminum (Al).

[0054] Moreover, as metal-based nanoparticles (X1), from the viewpoint of availability and economy, it is preferably selected from one or more of titanium dioxide (TiO2), manganese sulfide (MnS), iron oxide (FeO, Fe2O3), nickel oxide (NiO), copper oxide (CuO, Cu2O), zirconium oxide (ZrO2), molybdenum disulfide (MoS2), tungsten disulfide (WS2), zinc oxide (ZnO), boron nitride (BN), titanium nitride (TiN), and aluminum oxide (Al2O3).

[0055] Among them, from the viewpoint of improving the wear resistance of the composition (lubricating oil composition and grease composition), one or more selected from zirconium oxide (ZrO2), tungsten disulfide (WS2), zinc oxide (ZnO), and titanium nitride (TiN) are preferred.

[0056] <Polymer (Y)>

[0057] In the present embodiment, the polymer (Y) is a vinyl polymer having a linear alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group.

[0058] When the polymer (Y) does not have a linear alkyl group having 10 to 28 carbon atoms, oil solubility (solubility in low-polarity oils such as mineral oils and hydrocarbon oils) cannot be ensured.

[0059] In addition, it is presumed that the nitrogen-containing heterocyclic group plays a role in promoting the dispersibility of the metal nanoparticles (X) in the polymer (Y). Therefore, when the polymer (Y) does not have a nitrogen-containing heterocyclic group, the function of promoting excellent dispersibility of the metal nanoparticles (X) cannot be ensured.

[0060] Here, the number of carbon atoms of the chain alkyl group is preferably 11 to 26, more preferably 12 to 24, and even more preferably 13 to 22, from the viewpoint of more easily improving the oil solubility of the polymer (Y).

[0061] Specific examples of chain alkyl groups include decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, eicosyl, heneicosyl, docosyl, tricosyl, tetracosyl, pentacosyl, hexacosyl, heptacosyl, octacosyl, nonacosyl, eicosyl and the like.

[0062] The chain alkyl group may be a linear structure or a branched structure, but is preferably a linear structure from the viewpoint of more easily improving the oil solubility of the polymer (Y).

[0063] Examples of the nitrogen-containing heterocyclic group include 5-membered rings, 6-membered rings, bicyclic compounds and polymers containing a nitrogen atom. Specific examples of the nitrogen-containing heterocyclic group include, for example, a monovalent group obtained by removing one hydrogen atom from a nitrogen-containing heterocyclic ring such as a pyrrole ring, a pyrroline ring, a pyrrolidine ring, a pyrrolidone ring, a pyrazole ring, a pyrazoline ring, a pyrazolidine ring, an imidazole ring, an imidazoline ring, an imidazoline ring, a triazole ring, a tetrazole ring, an oxazole ring, an oxazoline ring, an oxazolidine ring, an isoxazole ring, an isoxazoline ring, an isoxazolidine ring, a thiazole ring, a thiazoline ring, a thiazolidine ring, an isothiazole ring, an isothiazolidine ring, a pyridine ring, a piperidine ring, a pyridazine ring, a pyrimidine ring, a pyrazine ring, a piperazine ring, a triazine ring, a morpholine ring, a thiomorpholine ring, a c-caprolactam ring, an indole ring, an indazole ring, a benzimidazole ring, a quinoline ring, an isoquinoline ring, a purine ring, a bipyridine ring, and a terpyridine ring.

[0064] Here, from the viewpoint of easily improving the effects of the present invention, the nitrogen-containing heterocyclic group is preferably a monovalent group obtained by removing one hydrogen atom from a pyrrolidone ring.

[0065] In addition, from the viewpoint of making it easier to improve the effect of the present invention, the polymer (Y) is preferably one or more selected from the group consisting of a polymer (Y1) and a polymer (Y2), wherein the polymer (Y1) comprises two or more selected from the group consisting of a constituent unit derived from the following monomer (ya), a constituent unit derived from the following monomer (yb), and a constituent unit derived from the following monomer (yc), and the polymer (Y2) comprises a constituent unit derived from the following monomer (yb) and does not contain a constituent unit derived from the following monomer (ya) and a constituent unit derived from the following monomer (yc),

[0066] ·Monomer (ya): Olefin having 12 to 30 carbon atoms

[0067] Monomer (yb): a vinyl monomer having a nitrogen-containing heterocyclic group in which at least one hydrogen atom is substituted by a chain alkyl group having 12 to 30 carbon atoms

[0068] Monomer (yc): a vinyl monomer having a nitrogen-containing heterocyclic group in which none of the hydrogen atoms is substituted by a linear alkyl group having 12 to 30 carbon atoms.

[0069] Hereinafter, the polymer (Y1) and the polymer (Y2) will be described in detail.

[0070] <Polymer (Y1)>

[0071] The polymer (Y1) contains two or more selected from the group consisting of a structural unit derived from the following monomer (ya), a structural unit derived from the following monomer (yb), and a structural unit derived from the following monomer (yc).

[0072] ·Monomer (ya): Olefin having 12 to 30 carbon atoms

[0073] Monomer (yb): a vinyl monomer having a nitrogen-containing heterocyclic group in which at least one hydrogen atom is substituted by a chain alkyl group having 12 to 30 carbon atoms

[0074] Monomer (yc): a vinyl monomer having a nitrogen-containing heterocyclic group in which none of the hydrogen atoms is substituted by a linear alkyl group having 12 to 30 carbon atoms.

[0075] In the present embodiment, the polymer (Y1) may contain other structural units in addition to the structural units derived from the monomer (ya), the structural units derived from the monomer (yb), and the structural units derived from the monomer (yc) within a range not impairing the effects of the present invention.

[0076] However, in the present embodiment, from the viewpoint of ensuring the oil solubility required for the polymer (Y1) and the dispersibility in the metal nanoparticles (X), the total content of two or more constituent units selected from the constituent units derived from the monomer (ya), the constituent units derived from the monomer (yb), and the constituent units derived from the monomer (yc) in the polymer (Y1) is preferably 50 mol% to 100 mol%, more preferably 60 mol% to 100 mol%, further preferably 70 mol% to 100 mol%, further preferably 80 mol% to 100 mol%, and further more preferably 90 mol% to 100 mol%, based on the total constituent units of the polymer (Y1).

[0077] Hereinafter, the monomer (ya), the monomer (yb), and the monomer (yc) will be described in detail.

[0078] (monomer (ya), constituent unit (YA))

[0079] The monomer (ya) used in the present embodiment is an olefin having 12 to 30 carbon atoms.

[0080] The structural unit (YA) derived from the monomer (ya) mainly plays a role in exerting oil solubility (solubility in low-polarity oils such as mineral oil and hydrocarbon oil) in the polymer (Y1).

[0081] Here, the number of carbon atoms of the monomer (ya) is preferably 13 to 28, more preferably 14 to 26, further preferably 15 to 24, and further preferably 16 to 22, from the viewpoint of more easily improving the oil solubility of the polymer (Y1).

[0082] Specific examples of preferred compounds as monomer (ya) include dodecene, tridecene, tetradecene, pentadecene, hexadecene, heptadecene, octadecene, nonadecene, eicosene, heneicosene, docosene, tricosene, tetracosene, pentacosene, hexacosene, heptacosene, octacosene, nonacosene, and triacontene.

[0083] The monomer (ya) may have a linear structure or a branched structure, but preferably has a linear structure from the viewpoint of more easily improving the oil solubility of the polymer (Y1).

[0084] In order to more easily improve the oil solubility of the polymer (Y1), the double bond site of the monomer (ya) is preferably present at positions 1 to 3, more preferably at position 1 or 2, and even more preferably at position 1. That is, the monomer (ya) is preferably an α-olefin.

[0085] Therefore, the monomer (ya) preferably contains a linear α-olefin, and more preferably contains a linear α-olefin having a carbon number of 12 to 30. The preferred carbon number of the linear α-olefin is as shown above.

[0086] The monomer (ya) may be used alone or in combination of two or more. Therefore, the polymer (Y1) may contain a constituent unit (YA) derived from the monomer (ya) alone or in combination of two or more.

[0087] (monomer (yb), constituent unit (YB))

[0088] The monomer (yb) used in the present embodiment is a vinyl monomer having a nitrogen-containing heterocyclic group in which at least one hydrogen atom is substituted by a chain alkyl group having 12 to 30 carbon atoms. The chain alkyl group having 12 to 30 carbon atoms in the structural unit (YB) derived from the monomer (yb) mainly plays the role of exerting oil solubility (solubility in low-polarity oils such as mineral oils and hydrocarbon oils) in the polymer (Y1).

[0089] The nitrogen-containing heterocyclic group in the structural unit (YB) derived from the monomer (yb) is presumed to play a role in promoting the dispersibility of the metal nanoparticles (X) in the polymer (Y1) and to play a role in stabilizing the polymer (Y1) in a high temperature environment.

[0090] From the viewpoint of more easily improving the oil solubility of the polymer (Y2), the number of carbon atoms of the chain alkyl group that replaces at least one hydrogen atom of the nitrogen-containing heterocyclic group is preferably 13 to 28, more preferably 14 to 26, further preferably 15 to 24, and further preferably 16 to 22.

[0091] Preferred chain alkyl groups include dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, eicosyl, henicosyl, docosyl, tricosyl, tetracosyl, pentacosyl, hexacosyl, heptacosyl, octacosyl, nonacosyl, and triacontyl.

[0092] The chain alkyl group may be a linear structure or a branched structure, but is preferably a linear structure from the viewpoint of more easily improving the oil solubility of the polymer (Y1).

[0093] Examples of the nitrogen-containing heterocyclic group include the same groups as exemplified as the nitrogen-containing heterocyclic group possessed by the polymer (Y).

[0094] Here, from the viewpoint of easily improving the effects of the present invention, the nitrogen-containing heterocyclic group is preferably a monovalent group obtained by removing one hydrogen atom from a pyrrolidone ring.

[0095] Therefore, the monomer (yb) is preferably a vinyl monomer having a monovalent group obtained by removing one hydrogen atom from a pyrrolidone ring in which at least one hydrogen atom is substituted with a chain alkyl group having 12 to 30 carbon atoms.

[0096] Specifically, the monomer (yb) is preferably a compound represented by the following general formula (1).

[0097] [Chemistry 1]

[0098]

[0099] In the above general formula (1), R 1 , R 2 , and R 3 Each independently represents a hydrogen atom or a chain alkyl group having 1 to 2 carbon atoms. 4 represents a chain alkyl group having 1 to 5 carbon atoms. 5 It represents a chain alkyl group having 12 to 30 carbon atoms. m is an integer of 0 to 2.

[0100] It should be noted that from the viewpoint of making it easier to enhance the effect of the present invention, R 1 , R 2 , and R 3 Preferably, it is a hydrogen atom. From the same viewpoint, m=0 is preferred. 5 Preferred embodiments of the chain alkyl group having 12 to 30 carbon atoms are as described above.

[0101] The monomer (yb) may be used alone or in combination of two or more. Therefore, the polymer (Y1) may contain a constituent unit (YB) derived from the monomer (yb) alone or in combination of two or more.

[0102] (monomer (yc), constituent unit (Yε))

[0103] The monomer (yc) used in the present embodiment is a vinyl monomer having a nitrogen-containing heterocyclic group in which none of the hydrogen atoms is substituted by a chain alkyl group having 12 to 30 carbon atoms.

[0104] It is estimated that the structural unit (Yε) derived from the monomer (yc) plays a role in achieving excellent dispersibility of the metal nanoparticles (X) in the polymer (Y1).

[0105] Examples of the nitrogen-containing heterocyclic group include the same groups as exemplified as the nitrogen-containing heterocyclic group possessed by the polymer (Y).

[0106] Here, from the viewpoint of easily improving the effects of the present invention, the nitrogen-containing heterocyclic group is preferably a monovalent group obtained by removing one hydrogen atom from a pyrrolidone ring.

[0107] Therefore, the monomer (yc) is preferably a vinyl monomer having a monovalent group obtained by removing one hydrogen atom from a pyrrolidone ring in which at least one hydrogen atom is substituted with a chain alkyl group having 12 to 30 carbon atoms.

[0108] Specifically, the monomer (yc) is preferably a compound represented by the following general formula (2).

[0109] [Chemistry 2]

[0110]

[0111] In the above general formula (2), R 6 , R 7 , and R 8 R each independently represents a hydrogen atom or a chain alkyl group having 1 to 2 carbon atoms. 9 It represents a chain alkyl group having 1 to 5 carbon atoms. n is an integer of 0 to 3.

[0112] It should be noted that from the viewpoint of making it easier to enhance the effect of the present invention, R 6 , R 7 , and R 8 A hydrogen atom is preferred. From the same viewpoint, n=0 is preferred.

[0113] The monomer (yc) may be used alone or in combination of two or more. Therefore, the polymer (Y1) may contain a constituent unit (YC) derived from the monomer (yc) alone or in combination of two or more.

[0114] (Preferred embodiment of polymer (Y1))

[0115] Examples of the polymer (Y1) include polymers containing structural units derived from the following monomers.

[0116] ·Monomer (ya) and monomer (yb)

[0117] ·Monomer (ya) and monomer (yc)

[0118] ·Monomer (yb) and monomer (yc)

[0119] ·Monomer (ya), monomer (yb), and monomer (yc)

[0120] By using the above combination, the polymer (Y1) can be a vinyl polymer having a linear alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group.

[0121] Here, among the above polymers, from the viewpoint of ensuring a balance between oil solubility and dispersibility of the metal nanoparticles (X), the polymer (Y1) is preferably a polymer comprising a structural unit (YA) derived from a monomer (ya) and a structural unit (YC) derived from a monomer (yc).

[0122] (Content ratio of constituent unit (YA) to constituent unit (YC))

[0123] When the polymer (Y1) is a polymer comprising a constituent unit (YA) derived from a monomer (ya) and a constituent unit (YC) derived from a monomer (yc), the content ratio [(YA) / (YC)] of the constituent unit (YA) derived from the monomer (ya) and the constituent unit (YC) derived from the monomer (yc) is preferably 10 / 90 to 95 / 5, more preferably 40 / 60 to 90 / 10, and further preferably 60 / 40 to 90 / 10 in terms of molar ratio, from the viewpoint of easily ensuring a balance between the oil solubility of the polymer (Y1) and the dispersibility in the metal-based nanoparticles (X).

[0124] <Polymer (Y2)>

[0125] The polymer (Y2) contains a structural unit derived from the above-mentioned monomer (yb), and does not contain a structural unit derived from the above-mentioned monomer (ya) and a structural unit derived from the above-mentioned monomer (yc).

[0126] The polymer (Y2) comprising the structural unit (YB) derived from the above-mentioned monomer (yb) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group, and is excellent in terms of ensuring a balance between oil solubility and ensuring the dispersibility of the metal-based nanoparticles (X).

[0127] In the present embodiment, polymer (Y2) can be composed only of the constituent unit (YB) derived from monomer (yb), but may also contain other constituent units other than the constituent unit (YB) within the scope of not damaging the effect of the present invention. However, it does not include the constituent unit derived from the above-mentioned monomer (ya) and the constituent unit derived from the above-mentioned monomer (yc). In this regard, it is clearly distinguished from polymer (Y1).

[0128] It should be noted that in the present embodiment, from the viewpoint of ensuring the required oil solubility of the polymer (Y2) and the dispersibility in the metal nanoparticles (X), the content of the constituent unit (YB) in the polymer (Y2) is preferably 70 mol% to 100 mol%, more preferably 80 mol% to 100 mol%, and further preferably 90 mol% to 100 mol%, based on all the constituent units of the polymer (Y2).

[0129] In addition, the preferred embodiment of the monomer (yb) is as described above, and the description thereof is omitted.

[0130] <Method for synthesizing polymer (Y)>

[0131] The polymer (Y) can be appropriately synthesized by, for example, homopolymerizing or copolymerizing the above-mentioned monomer components at a predetermined ratio according to a general method.

[0132] In addition, a commercially available product may be used as the polymer (Y), and examples of the commercially available product include Antaron V-220 (manufactured by Ashland Japan Co., Ltd.) and Antaron V-216 (manufactured by Ashland Japan Co., Ltd.).

[0133] <Content ratio of polymer (Y) and metal nanoparticles (X) [(Y) / (X)]>

[0134] In the composition of the present embodiment, from the viewpoint of facilitating good dispersion of the metal nanoparticles (X) in the dispersion medium, the content ratio of the polymer (Y) to the metal nanoparticles (X) [(Y) / (X)] is preferably 0.2 or more, more preferably 0.3 or more, in terms of mass ratio.

[0135] In addition, from the viewpoint of suppressing excessive use of the polymer (Y) and facilitating good dispersion of the metal nanoparticles (X) in the dispersion medium, the content ratio of the polymer (Y) to the metal nanoparticles (X) [(Y) / (X)] is preferably 10 or less, more preferably 6 or less, and even more preferably 3 or less in terms of mass ratio.

[0136] <Dispersion Medium>

[0137] Examples of the dispersion medium include one or more liquid dispersion media selected from organic solvents and lubricant base oils, and grease.

[0138] Examples of the organic solvent include nonpolar organic solvents such as alkanes. When a nonpolar organic solvent is used, the composition can be easily mixed and dispersed in a lubricating base oil when blended with a lubricating base oil of low polarity.

[0139] Examples of lubricating base oils include mineral oils; hydrocarbon synthetic oils such as polyolefins, isoparaffins, alkylbenzenes, and alkylnaphthalenes; GTL base oils obtained by isomerizing wax (Gas To Liquids (GTL) wax) produced from natural gas using the Fischer-Tropsch process or the like; and low-polar or non-polar lubricating base oils such as ether oils such as alkylated diphenyl ether and polyphenyl ether.

[0140] Examples of the grease include soap-based greases such as calcium-based grease, complex calcium-based grease, sodium-based grease, aluminum-based grease, complex aluminum-based grease, lithium-based grease, and complex lithium-based grease; non-soap-based inorganic greases such as organic bentonite grease and silicone grease; and non-soap-based organic greases such as polyurea grease.

[0141] <Content of Metal Nanoparticles (X) in Composition>

[0142] The content of the metal nanoparticles (X) in the composition is not particularly limited as long as good dispersibility of the metal nanoparticles (X) can be ensured in the dispersion medium. Based on the total amount of the composition, it is preferably 0.005% by mass or more, more preferably 0.010% by mass or more, further preferably 0.050% by mass or more, further preferably 0.10% by mass or more, and even more preferably 0.50% by mass or more. In addition, it is preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 10% by mass or less, and even more preferably 5% by mass or less.

[0143] The upper and lower limits of these numerical ranges may be arbitrarily combined. Specifically, it is preferably 0.005% to 30% by mass, more preferably 0.010% to 20% by mass, further preferably 0.050% to 10% by mass, further preferably 0.10% to 5% by mass, and even more preferably 0.50% to 5% by mass.

[0144] [Method for producing composition]

[0145] The method for producing the composition of the present embodiment is not particularly limited, and examples thereof include a method including the following step (1).

[0146] Step (1): a step of dispersing a precursor of metal nanoparticles (X) in the presence of a polymer (Y) and at least one liquid dispersion medium selected from an organic solvent and a lubricating base oil,

[0147] It should be noted that the so-called "precursor of metal nanoparticles (X)" refers to the raw material of the metal nanoparticles (X) constituting the composition of the present embodiment (the state before being dispersed in the dispersion medium). The "precursor of metal nanoparticles (X)" is formed into an agglomerate formed by a large amount of agglomeration of primary particles, and the agglomerate can be crushed / grinded, broken, etc. by performing a dispersion treatment to form a state in which metal nanoparticles (X) of a desired particle size are dispersed in the dispersion medium.

[0148] Examples of the apparatus for performing the dispersion treatment in step (1) include kneading machines such as roll mills and kneaders, high-pressure homogenizers such as ultrasonic dispersers and microfluidizers, and media dispersers such as paint shakers and bead mills.

[0149] Among them, from the viewpoint of easily reducing the particle size of the precursor of the metal nanoparticles (X) (the viewpoint of easily approaching the particle size of the primary particles), it is preferable to use a media disperser.

[0150] When a media disperser is used, the material of the medium is preferably ceramics such as zirconium oxide and titanium dioxide, polymer materials such as polyethylene and polyamide, metals, etc., and zirconium oxide is particularly preferred. In addition, from the viewpoint of fully miniaturizing the precursor of the metal-based nanoparticles (X), the diameter of the medium is preferably 3 μm or more, more preferably 10 μm or more, 20 μm or more, and preferably 500 μm or less, more preferably 300 μm or less, and further preferably 100 μm or less.

[0151] As for the dispersion treatment time, since the appropriate dispersion treatment time varies according to the size of the medium-type disperser, the amount of the medium put in, and the amount of the raw material put in, it cannot be generally stipulated. For example, when about 150g of the medium is put into a container of 100mL capacity and about 20 to 40g of the raw material is put in for dispersion treatment, as a standard for the dispersion treatment time, from the viewpoint of fully miniaturizing the precursor of the metal-based nanoparticle (X), it is preferably 0.3 hours or more, more preferably 1 hour or more, and from the viewpoint of the manufacturing efficiency of the microparticle water dispersion, it is preferably 10 hours or less, more preferably 5 hours or less.

[0152] As for the shear force during the dispersion treatment, the appropriate shear force during the appropriate dispersion treatment varies according to the size of the medium-type disperser, the amount of the medium put in, and the amount of the raw material put in, so it cannot be generally specified. For example, when about 150g of the medium is put into a container of 100mL capacity and about 20 to 40g of the raw material is put in for dispersion treatment, the dispersion treatment is carried out by stirring at preferably 1000rpm or more, more preferably 1300rpm or more, further preferably 1500rpm or more, and preferably 5000rpm or less, more preferably 4000rpm or less, and further preferably 3000rpm or less.

[0153] [Use of the composition]

[0154] The composition of the present embodiment has excellent dispersibility of the metal nanoparticles (X) even in a high temperature environment (for example, 200° C. or higher) assumed in the use of the lubricating oil composition. Therefore, the composition is useful as an additive composition for a lubricating oil composition.

[0155] Furthermore, the composition of the present embodiment has excellent dispersibility of the metal nanoparticles (X) even in grease, and is therefore useful as an additive composition for grease compositions.

[0156] Therefore, in the present embodiment, a method of using the composition of the present embodiment as an additive composition for a lubricating oil composition or a grease composition can be provided.

[0157] When the composition of the present embodiment is an additive composition for a lubricating oil composition or an additive composition for a grease composition, the dispersion medium is preferably at least one selected from an organic solvent and a lubricating base oil.

[0158] In addition, when the composition of the present embodiment is an additive composition for a lubricating oil composition or an additive composition for a grease composition, the additive composition can impart excellent wear resistance to the lubricating oil composition or the grease composition. Therefore, the composition of the present embodiment is useful as an anti-wear agent.

[0159] Therefore, in the present embodiment, a method of using the composition of the present embodiment as an anti-wear agent can be provided.

[0160] Furthermore, the composition of the present embodiment is also useful as a lubricating oil composition or a grease composition as described below.

[0161] [Lubricating oil composition]

[0162] The composition of the present embodiment can also be used as a lubricating oil composition.

[0163] Therefore, in the present embodiment, the following lubricating oil composition can be provided.

[0164] A lubricating oil composition comprising metal nanoparticles (X), a polymer (Y) and a lubricating oil base oil.

[0165] The polymer (Y) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group,

[0166] The metal nanoparticles (X) and the polymer (Y) are dispersed in a lubricating base oil.

[0167] In the lubricating oil composition of the present embodiment, from the viewpoint of improving the dispersibility of the metal-based nanoparticles (X) in the lubricating base oil and improving the wear resistance, the content of the metal-based nanoparticles (X) is preferably 0.005% by mass or more, more preferably 0.010% by mass or more, further preferably 0.050% by mass or more, further preferably 0.10% by mass or more, further more preferably 0.50% by mass or more, and even more preferably 0.80% by mass or more, based on the total amount of the lubricating oil composition. In addition, it is preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 2% by mass or less.

[0168] The upper limit and lower limit of these numerical ranges may be combined arbitrarily. Specifically, preferably 0.005% to 5% by mass, more preferably 0.010% to 5% by mass, further preferably 0.050% to 3% by mass, further preferably 0.10% to 3% by mass, further more preferably 0.50% to 2% by mass, and even more preferably 0.80% to 2% by mass.

[0169] In the lubricating oil composition of the present embodiment, from the viewpoint of improving the dispersibility of the metal-based nanoparticles (X) in the lubricating base oil, the content of the polymer (Y) is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, further preferably 0.10% by mass or more, further preferably 0.20% by mass or more, and further preferably 0.30% by mass or more, based on the total amount of the lubricating oil composition. In addition, it is preferably 10% by mass or less, more preferably 5% by mass or less, and further preferably 3% by mass or less.

[0170] The upper and lower limits of these numerical ranges may be combined arbitrarily. Specifically, it is preferably 0.01% to 10% by mass, more preferably 0.05% to 10% by mass, further preferably 0.10% to 5% by mass, further preferably 0.20% to 5% by mass, and further more preferably 0.30% to 3% by mass.

[0171] In the lubricating oil composition of the present embodiment, preferred aspects of the metal nanoparticles (X) and the polymer (Y), the preferred content ratio of the metal nanoparticles (X) and the polymer (Y), etc. are as described in the composition of the present embodiment.

[0172] In the lubricating oil composition of the present embodiment, from the viewpoint of easily improving wear resistance, the average particle size of the metal nanoparticles (X) is preferably less than 600 nm, more preferably 500 nm or less, further preferably 400 nm or less, further preferably 300 nm or less, further more preferably 200 nm or less, and further preferably 150 nm or less. In addition, it is usually 10 nm or more.

[0173] <Lubricant base oil>

[0174] The lubricating base oil may be any of the base oils listed as the dispersion medium in the composition of the present embodiment. However, the lubricating base oil may be a mixed base oil containing synthetic oils other than the base oils listed as the dispersion medium.

[0175] Examples of the other synthetic oil include one or more selected from various esters such as polyol esters and dibasic acid esters; and polyalkylene glycols.

[0176] It should be noted that the kinematic viscosity of the lubricating base oil at 100°C is preferably 1.0 mm 2 / s~50mm 2 / s, more preferably 2.0 mm 2 / s~30mm 2 / s, and more preferably 3.0 mm 2 / s~20mm 2 The viscosity index of the lubricating base oil is preferably 80 or more, more preferably 90 or more, and even more preferably 100 or more.

[0177] The kinematic viscosity and viscosity index of the lubricating base oil are values ​​measured or calculated in accordance with JIS K 2283:2000.

[0178] <Additives>

[0179] The lubricating oil composition of the present embodiment may further contain general additives compounded in lubricating oil compositions within the scope of the present invention. Examples of such additives include antioxidants, oiliness agents, detergents and dispersants, viscosity index improvers, rust inhibitors, metal deactivators, and defoamers. These may be used alone or in combination of two or more.

[0180] <Physical Properties of Lubricating Oil Composition>

[0181] (Kinematic viscosity, viscosity index)

[0182] The 100° C. kinematic viscosity of the lubricating oil composition of the present embodiment is preferably 1.0 mm 2 / s~50mm2 / s, more preferably 2.0 mm 2 / s~30mm 2 / s, more preferably 3.0 mm 2 / s~20mm 2 / s.

[0183] The viscosity index of the lubricating oil composition of the present embodiment is preferably 90 or more, more preferably 100 or more, and even more preferably 110 or more.

[0184] The kinematic viscosity and viscosity index of the lubricating oil composition are values ​​measured or calculated in accordance with JIS K 2283:2000.

[0185] (Abrasion resistance)

[0186] The lubricating oil composition of the present embodiment has a wear scar diameter (average) obtained by a wear test (using an unheated lubricating oil composition) described in the Examples described below, preferably 470 μm or less, more preferably 460 μm or less, further preferably 450 μm or less, further preferably 440 μm or less, and further more preferably 430 μm or less.

[0187] [Use of lubricating oil composition]

[0188] The lubricating oil composition of the present embodiment is excellent in wear resistance.

[0189] Therefore, the lubricating oil composition of the present embodiment can be suitably used in various applications, such as gear oil (manual transmission oil, differential oil, etc.), automatic transmission oil (automatic transmission oil, etc.), continuously variable transmission oil (belt-type CVT oil, toroidal CVT oil, etc.), power steering oil, shock absorber oil and motor oil, etc.; internal combustion engine (engine) oil for gasoline engine, diesel engine and gas engine, etc.; hydraulic oil; turbine oil; compressor oil; fluid bearing oil; rolling bearing oil; refrigeration oil, etc., and can be suitably used as a lubricating oil composition filled in devices used in these various applications and lubricating between the various parts of the devices.

[0190] [Lubricating method using lubricating oil composition]

[0191] Preferred examples of a lubrication method using the lubricating oil composition of the present embodiment include a method in which the lubricating oil composition is filled into a device used in the above-mentioned respective applications to lubricate between the respective components of the respective devices.

[0192] In addition, in the present embodiment, there is also provided a method of filling the lubricating oil composition into a device used in the above-mentioned respective applications and using the composition for lubrication between the respective parts of the respective devices.

[0193] [Method for producing lubricating oil composition]

[0194] Examples of the method for producing the lubricating oil composition of the present embodiment include the following production method 1 to the following production method 3.

[0195] (Manufacturing method 1)

[0196] A method for producing a lubricating oil composition, comprising the following step (S1):

[0197] Step (S1): a step of dispersing a precursor of metal nanoparticles (X) in the presence of a polymer (Y) and a lubricating base oil

[0198] In addition, general additives that can be added to a lubricating oil composition may be added simultaneously with the step (S1) or after the step (S1).

[0199] (Manufacturing method 2)

[0200] A method for producing a lubricating oil composition, comprising: the following step (S2-1) and the following step (S2-2),

[0201] Step (S2-1): a step of dispersing a precursor of metal nanoparticles (X) in the presence of a polymer (Y) and an organic solvent to prepare an additive composition for a lubricating oil composition

[0202] Step (S2-2): a step of volatilizing the organic solvent after mixing the lubricating base oil and the additive composition for the lubricating oil composition.

[0203] In addition, general additives that can be added to a lubricating oil composition may be added simultaneously with the step (S2-2) or after the step (S2-2).

[0204] (Manufacturing method 3)

[0205] A method for producing a lubricating oil composition, comprising: the following step (S3-1) and the following step (S3-2),

[0206] Step (S3-1): a step of dispersing a precursor of metal nanoparticles (X) in the presence of a polymer (Y) and a lubricating base oil to prepare an additive composition for a lubricating oil composition

[0207] Step (S3-2): a step of mixing the lubricating base oil and the additive composition for the lubricating oil composition

[0208] In addition, general additives that can be added to a lubricating oil composition may be added simultaneously with the step (S3-2) or after the step (S3-2).

[0209] [Grease composition]

[0210] The composition of this embodiment can also be used as a grease composition.

[0211] Therefore, in the present embodiment, the following grease composition can be provided.

[0212] A grease composition comprising metal nanoparticles (X), a polymer (Y) and grease,

[0213] The polymer (Y) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group,

[0214] The metal nanoparticles (X) and the polymer (Y) are dispersed in the grease.

[0215] In the grease composition of the present embodiment, from the viewpoint of improving the dispersibility of the metal nanoparticles (X) in the grease and improving the wear resistance, the content of the metal nanoparticles (X) is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more based on the total amount of the grease composition. It is also preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 6% by mass or less.

[0216] The upper limit and lower limit of these numerical ranges may be arbitrarily combined. Specifically, it is preferably 1% by mass to 10% by mass, more preferably 2% by mass to 8% by mass, and even more preferably 3% by mass to 6% by mass.

[0217] In the grease composition of the present embodiment, from the viewpoint of improving the dispersibility of the metal-based nanoparticles (X) in the grease, the content of the polymer (Y) is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, based on the total amount of the grease composition. It is also preferably 20% by mass or less, more preferably 16% by mass or less, and even more preferably 12% by mass or less.

[0218] The upper limit and lower limit of these numerical ranges may be arbitrarily combined. Specifically, it is preferably 1% by mass to 20% by mass, more preferably 2% by mass to 16% by mass, and still more preferably 3% by mass to 12% by mass.

[0219] It should be noted that in the grease composition of the present embodiment, the preferred embodiments of the metal nanoparticles (X) and the polymer (Y), the preferred content ratio of the metal nanoparticles (X) and the polymer (Y), etc. are as described in the composition of the present embodiment.

[0220] In the grease composition of the present embodiment, the metal nanoparticles (X) are not unevenly present in the grease composition, but are extremely uniformly dispersed. This can also be explained by the resistivity reduction effect when the titanium nitride nanoparticles and tungsten disulfide nanoparticles are dispersed in the examples. That is, it can be inferred that in the grease composition of the present embodiment, the tiny metal nanoparticles (X) are extremely uniformly dispersed, resulting in a certain interaction between the metal nanoparticles (X) that are close to each other, forming a high degree of network generated by the tiny metal nanoparticles (X). This highly dispersed state is considered to be a dispersed state that cannot be achieved in previous solid lubricants. It can be inferred that according to the highly dispersed state, various effects brought about by the metal nanoparticles (X), such as improved wear resistance and reduced resistivity, can be well exerted.

[0221] <Grease>

[0222] As the grease, those listed as the dispersion medium in the composition of the present embodiment can be used appropriately.

[0223] Among them, polyurea grease is preferably used from the viewpoint of heat resistance and the like.

[0224] Among polyurea greases, aliphatic diurea grease is more preferably used.

[0225] In addition, as the lubricating base oil constituting the grease, the substances listed as the dispersion medium in the present embodiment can be used as appropriate.

[0226] <Additives>

[0227] The grease composition of the present embodiment may contain general additives that can be blended into grease within the scope of the present invention.

[0228] Examples of such additives include antioxidants, rust inhibitors, extreme pressure agents, thickeners, solid lubricants, detergents and dispersants, corrosion inhibitors, and metal deactivators.

[0229] These additives may be used alone or in combination of two or more.

[0230] <Physical Properties of Grease Composition>

[0231] (Abrasion resistance)

[0232] The grease composition of the present embodiment has a wear scar diameter (average) of preferably 260 μm or less, more preferably 250 μm or less, and even more preferably 240 μm or less, as determined by a wear test described in Examples below.

[0233] (Coefficient of friction)

[0234] The grease composition of the present embodiment preferably has a friction coefficient of 0.100 or less, more preferably 0.090 or less, further preferably 0.080 or less, and further preferably 0.070 or less, as determined by a wear test described in Examples below.

[0235] (Volume resistivity)

[0236] The grease composition of the present embodiment preferably has a volume resistivity of less than 1.0×10 13 Ωcm, more preferably 1.5×10 12 Ωcm or less, more preferably 1.2×10 12 Ωcm or less.

[0237] [Application of grease composition]

[0238] The grease composition of this embodiment is excellent in wear resistance.

[0239] Therefore, the grease composition of the present embodiment can be suitably used in, for example, various bearings such as sliding bearings, rolling bearings, oil-containing bearings, fluid bearings, reducers, gears, internal combustion engines, brakes, parts for torque transmission devices, fluid joints, parts for compression devices, chains, parts for hydraulic devices, parts for vacuum pump devices, watch parts, parts for hard disks, parts for refrigerators, parts for cutting machines, parts for rolling mills, parts for deep drawing machines, parts for roll forming machines, parts for automobiles, parts for forging machines, parts for heat treatment machines, parts for heat media, parts for cleaning machines, parts for shock absorbers, parts for sealing devices, and the like.

[0240] In addition, when the grease composition of the present embodiment uses the metal nanoparticles (X) having excellent conductivity, the resistivity is low and the conductivity is excellent. Therefore, the grease composition of the present embodiment can be used to prevent electrical corrosion. In other words, the grease composition of the present embodiment can be used as a grease for preventing electrical corrosion.

[0241] Representative particles of the metal nanoparticles (X) having excellent conductivity include titanium nitride nanoparticles and tungsten disulfide nanoparticles. However, the metal nanoparticles (X) having excellent conductivity are not limited thereto, and particles made of a material having excellent conductivity may be appropriately used.

[0242] [Lubricating method using grease composition]

[0243] As a lubrication method using the grease composition of the present embodiment, preferably, there is mentioned a method of filling the grease composition into a device used in the above-mentioned respective applications and lubricating between the respective parts of the respective devices.

[0244] In addition, in the present embodiment, there is also provided a method of filling the grease composition into a device used in the above-mentioned respective applications and using the grease composition for lubrication between the respective parts of the respective devices.

[0245] [Method for producing grease composition]

[0246] Examples of the method for producing the grease composition of the present embodiment include the following production methods 4 to 8. Among them, the following production methods 5 to 8 are preferred from the viewpoint of the ease of production of the grease composition.

[0247] (Manufacturing method 4)

[0248] A method for producing a grease composition, comprising the following steps (S4-1) and (S4-2):

[0249] Step (S4-1): a step of dispersing a precursor of metal nanoparticles (X) in the presence of a polymer (Y) and an organic solvent to prepare an additive composition for a grease composition

[0250] Step (S4-2): a step of volatilizing the organic solvent after mixing the grease and the additive composition for the grease composition.

[0251] In addition, general additives that can be added to a grease composition may be added simultaneously with the step (S4-2) or after the step (S4-2).

[0252] The grease and the additive composition for the grease composition can be mixed together using, for example, a roll mill.

[0253] (Manufacturing method 5)

[0254] A method for producing a grease composition, comprising the following steps (S5-1) and (S5-2):

[0255] Step (S5-1): a step of dispersing a precursor of metal nanoparticles (X) in the presence of a polymer (Y) and a lubricating base oil to prepare an additive composition for a grease composition

[0256] Step (S5-2): a step of mixing the grease and the additive composition for the grease composition.

[0257] In addition, general additives that can be added to a grease composition may be added simultaneously with the step (S5-2) or after the step (S5-2).

[0258] The grease and the additive composition for the grease composition can be mixed together using, for example, a roll mill.

[0259] (Manufacturing method 6)

[0260] A method for producing a grease composition, comprising: the following step (S6-1), the following step (S6-2), and the following step (S6-3),

[0261] Step (S6-1): a step of dispersing a precursor of metal nanoparticles (X) in the presence of a polymer (Y) and an organic solvent to prepare an additive composition 1 using the organic solvent as a dispersion medium.

[0262] Step (S6-2): After mixing the lubricating base oil and the additive composition 1, the organic solvent is volatilized to prepare the additive composition 2 using the lubricating base oil as a dispersion medium.

[0263] Step (S6-3): a step of mixing the grease and the additive composition 2 described above.

[0264] In addition, general additives that can be added to a grease composition may be added simultaneously with the step (S6-3) or after the step (S6-3).

[0265] The grease and the additive composition 2 may be mixed, for example, using a roll mill or the like.

[0266] (Manufacturing method 7)

[0267] A method for producing a grease composition, comprising the following steps (S7-1) and (S7-2):

[0268] Step (S7-1): a step of dispersing a precursor of metal nanoparticles (X) in the presence of a polymer (Y) and a lubricating base oil to prepare an additive composition using the lubricating base oil as a dispersion medium.

[0269] Step (S7-2): a step of using the additive composition as the lubricating base oil (α) or mixing the additive composition with the lubricating base oil (α) when producing grease from the lubricating base oil (α) and the thickener (β).

[0270] In addition, general additives that can be added to a grease composition may be added simultaneously with the step (S7-2) or after the step (S7-2).

[0271] (Manufacturing method 8)

[0272] A method for producing a grease composition, comprising: the following step (S8-1), the following step (S8-2), and the following step (S8-3),

[0273] Step (S8-1): a step of dispersing a precursor of metal nanoparticles (X) in the presence of a polymer (Y) and an organic solvent to prepare an additive composition 1 using the organic solvent as a dispersion medium.

[0274] Step (S8-2): After mixing the lubricating base oil and the additive composition 1, the organic solvent is volatilized to prepare the additive composition 2 using the lubricating base oil as a dispersion medium.

[0275] Step (S8-3): a step of using the additive composition 2 as the lubricating base oil (α) or mixing the additive composition 2 with the lubricating base oil (α) when producing grease from the lubricating base oil (α) and the thickener (β).

[0276] In addition, general additives that can be added to a grease composition may be added simultaneously with the step (S8-3) or after the step (S8-3).

[0277] [One embodiment of the present invention provided]

[0278] In one embodiment of the present invention, the following [1] to

[15] can be provided.

[0279] [1] A composition comprising metal nanoparticles (X), a polymer (Y) and a dispersion medium,

[0280] The polymer (Y) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group,

[0281] The metal nanoparticles (X) and the polymer (Y) are dispersed in a dispersion medium,

[0282] The composition is used as an additive composition for a lubricating oil composition, an additive composition for a grease composition, a lubricating oil composition or a grease composition.

[0283] [2] The composition according to the above [1], wherein the metal-based nanoparticles (X) contain metal-based nanoparticles (X1), and the metal-based nanoparticles (X1) are metal nanoparticles formed from one or more metal elements (x1) selected from transition metal elements and metal elements and semi-metal elements of Groups 12 to 15, nanoparticles formed from oxides of the metal element (x1), nanoparticles formed from nitrides of the metal element (x1), nanoparticles formed from sulfides of the metal element (x1), nanoparticles formed from carbides of the metal element (x1), and nanoparticles formed from borides of the metal element (x1).

[0284] [3] The composition according to [1] or [2] above, wherein the polymer (Y) is one or more selected from a polymer (Y1) and a polymer (Y2), the polymer (Y1) comprises two or more selected from a constituent unit derived from the following monomer (ya), a constituent unit derived from the following monomer (yb), and a constituent unit derived from the following monomer (yc), and the polymer (Y2) comprises a constituent unit derived from the following monomer (yb),

[0285] ·Monomer (ya): Olefin having 12 to 30 carbon atoms

[0286] Monomer (yb): a vinyl monomer having a nitrogen-containing heterocyclic group in which at least one hydrogen atom is substituted by a chain alkyl group having 12 to 30 carbon atoms

[0287] Monomer (yc): a vinyl monomer having a nitrogen-containing heterocyclic group in which none of the hydrogen atoms is substituted by a linear alkyl group having 12 to 30 carbon atoms.

[0288] [4] The composition according to [3] above, wherein the polymer (Y1) comprises a structural unit derived from the monomer (ya) and a structural unit derived from the following monomer (yc).

[0289] [5] The composition according to [3] or [4] above, wherein the monomer (ya) comprises a linear α-olefin having 12 to 30 carbon atoms.

[0290] [6] The composition according to any one of [1] to [5] above, wherein the nitrogen-containing heterocyclic group is a monovalent group obtained by removing one hydrogen atom from a pyrrolidone ring.

[0291] [7] The composition according to any one of [1] to [6] above, wherein the content ratio [(Y) / (X)] of the polymer (Y) to the metal nanoparticles (X) is 0.2 or more in terms of mass ratio.

[0292] [8] The method for producing a composition according to any one of [1] to [7] above, comprising the following step (1):

[0293] Step (1): a step of dispersing a precursor of metal nanoparticles (X) in the presence of a polymer (Y) and at least one liquid dispersion medium selected from an organic solvent and a lubricating base oil,

[0294] The polymer (Y) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group.

[0295] [9] The composition according to any one of [1] to [7] above, wherein the composition is an additive composition for the lubricating oil composition or an additive composition for the grease composition,

[0296] The dispersion medium is at least one selected from an organic solvent and a lubricating base oil.

[0297]

[10] The composition according to the above [9], which is used as an anti-wear agent.

[0298]

[11] A lubricating oil composition comprising metal nanoparticles (X), a polymer (Y) and a lubricating oil base oil,

[0299] The polymer (Y) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group,

[0300] The metal nanoparticles (X) and the polymer (Y) are dispersed in a lubricating base oil.

[0301]

[12] The lubricating oil composition according to

[11] above, wherein the average particle size of the metallic nanoparticles (X) is less than 600 nm.

[0302]

[13] A grease composition comprising metal nanoparticles (X), a polymer (Y) and a grease,

[0303] The polymer (Y) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group,

[0304] The metal nanoparticles (X) and the polymer (Y) are dispersed in the grease.

[0305]

[14] The grease composition according to

[13] above, wherein the volume resistivity is less than 1.0×10 13 Ωcm.

[0306]

[15] The grease composition according to

[14] above, which is used for preventing electrical corrosion.

[0307] Example

[0308] The present invention will be specifically described by the following examples, but the present invention is not limited to the following examples.

[0309] 1. Research on the dispersibility of metal nanoparticles (X)

[0310] The effect of polymer type on the dispersibility of metal nanoparticles (X) was studied.

[0311] <Raw Materials>

[0312] Details of the additive composition for lubricating oil compositions (hereinafter also referred to as “additive composition”) and the organic solvent, lubricating oil base oil, metallic nanoparticles (X), and polymer used in producing the lubricating oil composition in “1. Study on the dispersibility of metallic nanoparticles (X)” are shown below.

[0313] (Organic Solvent)

[0314] n-heptane was used and will be abbreviated as "heptane" in the following description.

[0315] (Lubricant base oil)

[0316] Hydrocarbon mineral oil (40°C kinematic viscosity: 17.8 mm 2 / s).

[0317] The 40° C. kinematic viscosity of the lubricating base oil was measured in accordance with JIS K 2283:2000.

[0318] (Precursor of Metal Nanoparticles (X))

[0319] "ZnO": zinc oxide nanoparticles (manufactured by IoLiTec, trade name: zinc oxide, model: NO-0011-HP, primary particle size = 20 nm)

[0320] (Polymer (Y)

[0321] "Polymer (Y1)": Antaron V-220 (manufactured by Ashland Japan Co., Ltd.)

[0322] Antaron V-220 is a copolymer of 1-eicosene and N-vinylpyrrolidone.

[0323] "Polymer (Y2)": Antaron V-216 (manufactured by Ashland Japan Co., Ltd.)

[0324] Antaron V-216 is a polymer of a compound in which one of the hydrogen atoms not bonded to the nitrogen atom constituting N-vinylpyrrolidone (hydrogen atoms bonded to the carbon atom constituting the heterocyclic ring) is substituted with a hexadecyl group.

[0325] (Polymer (Y')

[0326] "Polymer (Y'1)": Malialim AWS-0851 (manufactured by NOF Corporation, high molecular weight polycarboxylic acid)

[0327] "Polymer (Y'2)": a copolymer of methyl methacrylate, N-(3-dimethylaminopropyl)methacrylamide, and dodecyl methacrylate (hereinafter referred to as "acrylate polymer")

[0328] · "Polymer (Y'3)": Esleam AD-508E (manufactured by NOF Corporation, high molecular weight amine compound)

[0329] "Polymer (Y'4)": SOLSPERSE 76500 (manufactured by Lubrisol Co., Ltd., comb-shaped urethane dispersant)

[0330] · "Polymer (Y'5)": Emulgen A-90 (manufactured by Kao Corporation, polyoxyethylene distyrenated phenyl ether)

[0331] "Polymer (Y'6)": Malialim AAB-0851 (manufactured by NOF Corporation, high molecular weight polycarboxylic acid)

[0332] [Manufacturing Examples 1-1 to 1-3, Comparative Manufacturing Examples 1-1 to 1-6]

[0333] The additive composition for a lubricating oil composition (hereinafter also simply referred to as “additive composition”) and a method for producing the lubricating oil composition in “1. Study on dispersibility of metallic nanoparticles (X)” are shown below.

[0334] In the following production examples, the additive composition was prepared so that the content of the metal nanoparticles (X) was 1 mass % (based on the total amount of the additive composition) and the content of the polymer was 2 mass % (based on the total amount of the additive composition).

[0335] In the following production examples, the lubricating oil composition was prepared so that the content of the metal nanoparticles (X) was 1 mass % (based on the total amount of the lubricating oil composition) and the content of the polymer was 2 mass % (based on the total amount of the lubricating oil composition).

[0336] <Production Example 1-1>

[0337] (Production Example A1-1: Preparation of Additive Composition (A1-1))

[0338] 31.0 g of heptane, 0.32 g of ZnO, 0.64 g of polymer (Y2), and 152 g of zirconia beads (1) (particle size: 0.05 mm) were placed in a zirconia container (100 mL capacity), and a bead mill treatment was performed at 2000 rpm for 1.5 hours. The bead mill treatment was performed at room temperature (25° C.). Next, the liquid obtained by the bead mill treatment was filtered through a metal mesh filter to remove the zirconia beads, thereby obtaining an additive composition (A1-1).

[0339] (Production Example B1-1: Preparation of Lubricating Oil Composition (B1-1))

[0340] A portion of the additive composition (A1-1) is separated and added to the lubricating base oil and mixed so that the metal nanoparticles (X) and the polymer in the final lubricating oil composition are in the above-mentioned contents, and then the heptane is volatilized to obtain a lubricating oil composition (B1-1).

[0341] <Production Example 1-2>

[0342] (Production Example A1-2: Preparation of Additive Composition (A1-2))

[0343] The zirconia beads (1) were replaced with 152 g of zirconia beads (2) (particle size: 0.10 mm), and an additive composition (A1-2) was obtained in the same manner as in Production Example A1-1.

[0344] (Production Example B1-2: Preparation of Lubricating Oil Composition (B1-2))

[0345] The additive composition (A1-1) was replaced with the additive composition (A1-2), and a lubricating oil composition (B1-2) was obtained in the same manner as in Production Example B1-1.

[0346] <Production Example 1-3>

[0347] (Production Example A1-3: Preparation of Additive Composition (A1-3))

[0348] An additive composition (A1-3) was obtained by the same method as in Production Example A1-1 except that the polymer (Y2) was replaced by the polymer (Y1).

[0349] (Production Example B1-3: Preparation of Lubricating Oil Composition (B1-3))

[0350] The additive composition (A1-1) was replaced with the additive composition (A1-3), and a lubricating oil composition (B1-3) was obtained in the same manner as in Production Example B1-1.

[0351] <Comparative Production Example 1-1>

[0352] (Comparative Production Example A'1-1: Preparation of Additive Composition (A'1-1))

[0353] The polymer (Y2) was replaced by the polymer (Y'1), and the zirconia beads (1) were replaced by 152 g of zirconia beads (2) (particle size: 0.10 mm), and an additive composition (A'1-1) was obtained in the same manner as in Production Example A1-1.

[0354] (Production Example B'1-1: Preparation of Lubricating Oil Composition (B'1-1))

[0355] The additive composition (A1-1) was replaced with the additive composition (A′1-1), and a lubricating oil composition (B′1-1) was obtained in the same manner as in Production Example B1-1.

[0356] <Comparative Production Example 1-2>

[0357] (Comparative Production Example A'1-2: Preparation of Additive Composition (A'1-2))

[0358] The polymer (Y2) was replaced by the polymer (Y'2), and the zirconia beads (1) were replaced by 152 g of zirconia beads (2) (particle size: 0.10 mm), and an additive composition (A'1-2) was obtained in the same manner as in Production Example A1-1.

[0359] (Production Example B'1-2: Preparation of Lubricating Oil Composition (B'1-2))

[0360] The additive composition (A-1) was replaced with the additive composition (A'1-2), and a lubricating oil composition (B'1-2) was obtained in the same manner as in Production Example B1-1.

[0361] <Comparative Production Examples 1-3>

[0362] (Comparative Production Example A'1-3: Preparation of Additive Composition (A'1-3))

[0363] The polymer (Y2) was replaced by the polymer (Y'3), and the zirconia beads (1) were replaced by 152 g of zirconia beads (2) (particle size: 0.10 mm), and an additive composition (A'1-3) was obtained in the same manner as in Production Example A1-1.

[0364] <Comparative Production Examples 1-4>

[0365] (Comparative Production Example A'1-4: Preparation of Additive Composition (A'1-4))

[0366] The polymer (Y2) was replaced by the polymer (Y'4), and the zirconia beads (1) were replaced by 152 g of zirconia beads (2) (particle size: 0.10 mm), and an additive composition (A'1-4) was obtained in the same manner as in Production Example A1-1.

[0367] <Comparative Production Examples 1-5>

[0368] (Comparative Production Example A'1-5: Preparation of Additive Composition (A'1-5))

[0369] The polymer (Y2) was replaced by the polymer (Y'5), and the zirconia beads (1) were replaced by 152 g of zirconia beads (2) (particle size: 0.10 mm), and an additive composition (A'1-5) was obtained in the same manner as in Production Example A1-1.

[0370] <Comparative Production Example 1-6>

[0371] (Comparative Production Example A'1-6: Preparation of Additive Composition (A'1-6))

[0372] The polymer (Y2) was replaced with the polymer (Y'6), and the zirconia beads (1) were replaced with 152 g of zirconia beads (2) (particle size: 0.10 mm), and an additive composition (A'1-6) was obtained in the same manner as in Production Example A1-1.

[0373] [Examples 1-1 to 1-3, Comparative Examples 1-1 to 1-6]

[0374] The following examinations were conducted on each additive composition and each lubricating oil composition obtained in the above-mentioned Production Examples.

[0375] <Dispersibility Study 1: Dispersion State Study in Additive Composition>

[0376] The dispersion state of the metal nanoparticles (X) in each additive composition obtained in Production Examples A1-1 to A1-3 and Production Examples A'1-1 to A'1-6 (in heptane) was visually confirmed and evaluated based on the following criteria.

[0377] Evaluation A: No precipitation was observed and the dispersibility was extremely good.

[0378] Evaluation B: Although precipitation was slightly observed, dispersibility was good.

[0379] Evaluation C: Precipitation was observed and dispersibility was poor.

[0380] In "Dispersibility Study 1", additive compositions evaluated as A or B were considered to be acceptable.

[0381] In addition, for the additive composition evaluated as A or B, the average particle size of the metal nanoparticles (X) in the additive composition (in heptane) was measured. In this example, the average particle size of the metal nanoparticles (X) dispersed in the dispersion medium was measured by a dynamic light scattering method using a Zetasizer Nano ZS manufactured by Malvern. The measurement temperature was set to 25°C. As described above, the "average particle size" refers to the particle size of the cumulative value Z-average in the particle size distribution obtained by the dynamic light scattering method.

[0382] <Study on Dispersibility 2: Study on Long-term Stability of Dispersed State in Lubricating Oil Composition>

[0383] Lubricating oil compositions (B1-1) to (B1-3), (B'1-1), and (B'1-2) were respectively placed in transparent containers and left to stand at room temperature (25°C), and the long-term stability of the dispersion state of the metallic nanoparticles (X) in the lubricating oil compositions (in the lubricating oil base oil) was evaluated according to the following criteria.

[0384] Evaluation A: No precipitation was observed for 30 days or more.

[0385] Evaluation B: Precipitation was not observed for 2 days or more, but precipitation was observed before 30 days had passed.

[0386] Evaluation C: Precipitation was observed before 2 days had passed.

[0387] In the "Dispersibility Study 2", the lubricating oil composition evaluated as A was considered to be acceptable.

[0388] <Dispersion Study 3: Study of Dispersion State in High Temperature Environment>

[0389] A thin film heating test was performed on the lubricating oil compositions (B1-1) to (B1-3) and (B'1-2), and the dispersion state of the metallic nanoparticles (X) after heating was examined.

[0390] The thin film heating test was conducted by placing 3 cc of the lubricating oil composition in a glass cylindrical container having an inner diameter of 5 cm and heating the composition in a thin film liquid state in a thermostatic bath in air under the following conditions (1) or (2).

[0391] Condition (1): Heating at 220°C for 12 hours

[0392] Condition (2): Heating at 220°C for 3 hours, then heating at 250°C for 1 hour

[0393] The presence or absence of precipitation in the lubricating oil composition after the thin film heating test was visually confirmed, and the evaluation was A when no precipitation was observed, and B when precipitation was observed.

[0394] In addition, for the lubricating oil composition of evaluation A in which no precipitation was observed, the average particle size of the metal nanoparticles (X) in the lubricating oil composition was measured. The average particle size of the metal nanoparticles (X) in the lubricating oil composition was measured by the same method as described in "Dispersibility Study 1".

[0395] In "Dispersibility Study 3", the case where both conditions (1) and (2) were evaluated as A was considered as passing.

[0396] The results are shown in Tables 1 and 2.

[0397] [Table 1]

[0398] Table 1

[0399]

[0400] *1 The numerical values ​​in parentheses are the average particle size of the metal nanoparticles (X) in the lubricating oil composition (in the lubricating oil base oil).

[0401] [Table 2]

[0402] Table 2

[0403]

[0404] ※1The values ​​in parentheses are the average particle size of the metal nanoparticles (X) in the lubricant composition (lubricant base oil).

[0405] The following can be seen from the results shown in Tables 1 and 2.

[0406] "Dispersibility Study 1", "Dispersibility Study 2", and "Dispersibility Study 3" of Examples 1-1 to 1-3 using the polymer (Y1) or (Y2) all satisfied the acceptance criteria.

[0407] On the other hand, Comparative Examples 1-3 to 1-6 using polymers (Y'3) to (Y'6) did not meet the pass standard of "Study 1 of Dispersibility".

[0408] In addition, although Comparative Example 1-1 using the polymer (Y'1) satisfied the pass standard of "Dispersibility Study 1", it failed to satisfy the pass standard of "Dispersibility Study 2".

[0409] In addition, although Comparative Example 1-2 using polymer (Y'2) met the passing standards of "Dispersibility Study 1" and "Dispersibility Study 2", it did not meet the passing standard of "Dispersibility Study 3". From the measurement results of the average particle size of the metal nanoparticles (X) in the thin film heating test condition (1) of Comparative Example 1-2, it can be seen that when an acrylic acid ester polymer is used, the dispersibility deteriorates when heated at a high temperature, and the metal nanoparticles (X) are easily aggregated and cannot maintain a small particle size.

[0410] From the above results, it can be seen that by using the polymer (Y1) or (Y2), the metal nanoparticles (X) can be well dispersed in the dispersion medium, and the metal nanoparticles (X) can be stably dispersed in the dispersion medium for a long period of time even in a high temperature environment expected during use of the lubricating oil composition.

[0411] 2. Research on wear resistance (1)

[0412] The wear resistance of the lubricating oil composition in which the metal nanoparticles (X) are dispersed was examined.

[0413] [Examples 2-1 to 2-2, Comparative Example 2-1]

[0414] Wear tests were conducted on the lubricating oil compositions (B1-1), (B1-2), and (B′1-2) produced in “1. Study on dispersibility of metallic nanoparticles (x)” by the method described below.

[0415] <Wear test>

[0416] A high-speed reciprocating friction tester TE77 (manufactured by Phoenix Tribology) was used to introduce a lubricating oil composition between a test plate and a test ball. The test ball was moved under the following conditions to conduct the test. The longitudinal wear scar diameter and the transverse wear scar diameter of the test ball after the test were measured, and the average wear scar diameter was calculated using the following formula.

[0417] Test plate material: SUJ2, shape: length 58mm × width 38mm × thickness 3.9mm

[0418] Test ball material: SUJ2, diameter 10mm

[0419] Oil supply conditions: oil bath, oil volume 3mL

[0420] Load: 50N (300 seconds) → 100N (300 seconds) → 150N (300 seconds) → 200N (300 seconds)

[0421] Temperature: 100℃

[0422] Amplitude: 10mm

[0423] Frequency: 10Hz

[0424] Average wear scar diameter = {(longitudinal wear scar diameter) + (lateral wear scar diameter)} / 2

[0425] It can be said that the smaller the value of the wear scar diameter is, the more excellent the lubricating oil composition is in wear resistance.

[0426] It should be noted that the wear test was carried out under the following conditions (1) and (2).

[0427] Condition (1): An unheated lubricating oil composition is used.

[0428] Condition (2): A lubricating oil composition heated at 220° C. for 12 hours was used.

[0429] The results are shown in Table 3.

[0430] [Table 3]

[0431] Table 3

[0432]

[0433] From the results shown in Table 3, the following can be known.

[0434] It is understood that Examples 2-1 and 2-2 using the polymer (Y2) have small wear scar diameters and excellent wear resistance under both conditions (1) and (2).

[0435] In contrast, it is found that the wear scar diameter of Comparative Example 2-1 using polymer (Y'2) becomes larger under condition (2). This is believed to be because heating the lubricating oil composition facilitates aggregation of the metal nanoparticles (X), significantly reducing the wear resistance imparting effect of the metal nanoparticles (X).

[0436] 3. Research on wear resistance (2)

[0437] Following “2. Study on Wear Resistance (1)”, the wear resistance of the lubricating oil composition in which the metal-based nanoparticles (X) are dispersed was further studied.

[0438] <Raw Materials>

[0439] Details of the organic solvent, lubricating base oil, metallic nanoparticles (X), and polymer used in producing the lubricating oil composition in “3. Study on Wear Resistance (2)” are shown below.

[0440] (Organic Solvent)

[0441] Heptane was used.

[0442] (Lubricant base oil)

[0443] Similar to "1. Study on the dispersibility of metal nanoparticles (X)", a hydrocarbon mineral oil (40°C kinematic viscosity: 17.8 mm 2 / s).

[0444] (Precursor of Metal Nanoparticles (X))

[0445] "ZnO": zinc oxide nanoparticles (manufactured by IoLiTec, trade name: zinc oxide, model number: NO-0011-HP)

[0446] "ZrO2 (1)": zirconium oxide nanoparticles (manufactured by Kanto Denka Kogyo Co., Ltd., trade name: zirconium oxide particles, lot number: 210125-011, primary particle size = 8 nm)

[0447] "ZrO2(2)": zirconium oxide nanoparticles (manufactured by Aldrich, trade name: zirconium oxide nanopowder, model: 544760, primary particle size = 100 nm)

[0448] "WS2": tungsten disulfide nanoparticles (manufactured by IoLiTec, supplier code = NC-0016-HP, primary particle size = 90 nm, purity 99%)

[0449] (Polymer (Y)

[0450] "Polymer (Y1)": Antaron V-220 (manufactured by Ashland Japan Co., Ltd.)

[0451] "Polymer (Y2)": Antaron V-216 (manufactured by Ashland Japan Co., Ltd.)

[0452] [Production Examples 3-1 to 3-8, Comparative Production Examples 3-1 to 3-3]

[0453] The method for producing the lubricating oil composition in "3. Study on Wear Resistance (2)" is as follows.

[0454] (Production Example 3-1: Preparation of Lubricating Oil Composition (B3-1))

[0455] 31.0 g of lubricating base oil, 0.32 g of ZnO, 0.64 g of polymer (Y2), and 152 g of zirconium oxide beads (1) (particle size: 0.05 mm) were placed in a zirconium oxide container (100 mL capacity) and subjected to a bead mill treatment at 2000 rpm for 1.5 hours. The bead mill treatment was carried out at room temperature (25° C.). Next, the liquid obtained by the bead mill treatment was filtered using a metal mesh filter to remove the zirconium oxide beads, thereby obtaining a lubricating oil composition (B3-1).

[0456] (Production Example 3-2: Preparation of Lubricating Oil Composition (B3-2))

[0457] A lubricating oil composition (B3-2) was obtained in the same manner as in Production Example 3-1 except that the zirconia beads (1) were replaced with 152 g of zirconia beads (2) (particle size: 0.10 mm).

[0458] (Production Example 3-3: Preparation of Lubricating Oil Composition (B3-3))

[0459] In a zirconia container (100 mL capacity), 31.0 g of heptane, 0.32 g of ZrO2 (1), 0.64 g of polymer (Y2), and 152 g of zirconia beads (1) (particle size: 0.05 mm) were placed and subjected to a bead mill treatment at 2000 rpm for 1.5 hours. The bead mill treatment was carried out at room temperature (25° C.). Next, the liquid obtained by the bead mill treatment was filtered through a metal mesh filter to remove the zirconia beads, thereby obtaining an additive composition (A3-3).

[0460] Next, a portion of the additive composition (A3-3) was separated and added to the lubricating base oil and mixed so that the metal nanoparticles (X) and the polymer in the final lubricating oil composition would have the contents shown in Table 4, and then the heptane was volatilized to obtain a lubricating oil composition (B3-3).

[0461] (Production Example 3-4: Preparation of Lubricating Oil Composition (B3-4))

[0462] A lubricating oil composition (B3-4) was obtained in the same manner as in Production Example 3-3 except that the polymer (Y2) was replaced with the polymer (Y1).

[0463] (Manufacturing Example 3-5: Preparation of Lubricating Oil Composition (B3-5))

[0464] A lubricating oil composition (B3-5) was obtained in the same manner as in Production Example 3-4 except that the amount of polymer (Y1) added was changed to 0.32 g.

[0465] (Manufacturing Example 3-6: Preparation of Lubricating Oil Composition (B3-6))

[0466] A lubricating oil composition (B3-6) was obtained in the same manner as in Production Example 3-4 except that the zirconia beads (1) were replaced with 152 g of zirconia beads (2) (particle size: 0.10 mm).

[0467] (Manufacturing Example 3-7: Preparation of Lubricating Oil Composition (B3-7))

[0468] ZrO2(1) was changed to ZrO2(2), the addition amount of polymer (Y1) was changed to 0.13 g, zirconia beads (1) were changed to 152 g of zirconia beads (3) (particle size: 0.20 mm), and a lubricating oil composition (B3-7) was obtained using the same method as in Production Example 3-4.

[0469] (Manufacturing Example 3-8: Preparation of Lubricating Oil Composition (B3-8))

[0470] A lubricating oil composition (B3-8) was obtained in the same manner as in Production Example 3-3 except that ZnO (1) was replaced with WS2 and zirconia beads (1) were replaced with 152 g of zirconia beads (3) (particle size: 0.20 mm).

[0471] (Comparative Production Example 3-1: Preparation of Lubricating Oil Composition (B'3-1))

[0472] 99 mass % of the lubricating base oil and 1 mass % of the polymer (Y1) were mixed to obtain a lubricating oil composition (B'3-1).

[0473] (Comparative Production Example 3-2: Preparation of Lubricating Oil Composition (B'3-2))

[0474] 99.39 mass % of the lubricating base oil and 0.61 mass % of zinc dialkyldithiophosphate (ZnDTP) were mixed to obtain a lubricating oil composition (B'3-2).

[0475] (Comparative Production Example 3-3: Preparation of Lubricating Oil Composition (B'3-3))

[0476] 99.95 mass % of the lubricating base oil and 0.05 mass % of the zirconium complex were mixed to obtain a lubricating oil composition (B'3-3).

[0477] [Examples 3-1 to 3-8, Comparative Examples 3-1 to 3-4]

[0478] The lubricating oil compositions and lubricating oil base oils obtained in the above-mentioned manufacturing examples were subjected to the same wear test as in "2. Study on Wear Resistance (1)" (only condition (1) was used), and the wear scar diameter was measured. The test results were considered acceptable if the wear scar diameter (average) was 470 μm or less.

[0479] The average particle size of the metallic nanoparticles (X) in the lubricating oil composition (in the lubricating base oil) was measured by the same method as the measurement method described in “1. Study on the dispersibility of metallic nanoparticles (X)”.

[0480] The results are shown in Tables 4 and 5.

[0481] [Table 4]

[0482] Table 4

[0483]

[0484] [Table 5]

[0485] Table 5

[0486]

[0487] The following can be seen from Tables 4 and 5.

[0488] It can be seen that in Examples 3-1 to 3-8, the wear scar diameter (average) was 470 μm or less, and the wear resistance was excellent.

[0489] On the other hand, it can be seen that in Comparative Examples 3-1 to 3-4, the wear scar diameter (average) was larger than 470 μm, indicating that the wear resistance was poor.

[0490] Here, it can be seen that ZnDTP and the zirconium complex used in Comparative Examples 3-3 to 3-4 are anti-wear agents generally blended in lubricating oil compositions, but in this example, wear resistance exceeding that of these anti-wear agents can be obtained.

[0491] 4. Research on grease composition

[0492] Various studies have been conducted on the effects of adding an additive composition for a grease composition (hereinafter also simply referred to as “additive composition”) to a grease composition.

[0493] <Raw Materials>

[0494] Details of the organic solvent, lubricating base oil, metal nanoparticles (X), polymer, and grease used in producing the grease composition in “4. Study on Grease Composition” are shown below.

[0495] (Organic Solvent)

[0496] Heptane was used.

[0497] (Lubricant base oil)

[0498] Alkyl diphenyl ether (Moresco Hilube LB-100 manufactured by Moresco Corporation) was used.

[0499] (Precursor of Metal Nanoparticles (X))

[0500] "TiN": Titanium nitride nanoparticles (manufactured by EM Japan Co., Ltd., primary particle size = 20 nm, purity = 99.2% or more)

[0501] "WS2": tungsten disulfide nanoparticles (manufactured by IoLiTec, supplier code = NC-0016-HP, primary particle size = 90 nm, purity 99%)

[0502] (Metallic powder (X'))

[0503] "Powdered TiN": Titanium nitride particles with an average particle size of 2 μm

[0504] "Powder WS2": Titanium nitride particles with an average particle size of 2 μm

[0505] "Carbon black": Carbon particles with an average particle size of 2 μm

[0506] (Polymer (Y))

[0507] "Polymer (Y2)": Antaron V-216 (manufactured by Ashland Japan Co., Ltd.)

[0508] (Polymer (Y'))

[0509] "Polymer (Y'2)": Acrylate polymer

[0510] (Basic grease)

[0511] A base grease having an alkylated diphenyl ether as the base oil (the same base oil as the above-mentioned lubricant base oil) and an aliphatic diurea as the thickener was used. The mixing ratio of the thickener to the base oil was 1:5 by mass.

[0512] In addition, the aliphatic diurea is assumed to be an aliphatic diurea synthesized from octylamine and diphenylmethane diisocyanate.

[0513] [Manufacturing Examples 4-1 to 4-2, Comparative Manufacturing Examples 4-1 to 4-4]

[0514] The method for producing the grease composition in “4. Study on grease composition” is shown below.

[0515] <Production Example 4-1: Preparation of Grease Composition (C4-1)>

[0516] (Production Example A4-1: Preparation of Additive Composition (A4-1))

[0517] 17.6 g of heptane, 4.8 g of TiN, 9.6 g of polymer (Y2), and 152 g of zirconia beads (particle size: 0.05 mm) were placed in a zirconia container (100 mL capacity), and a bead mill treatment was performed at 2000 rpm for 1.5 hours. The bead mill treatment was performed at room temperature (25° C.). Next, the liquid obtained by the bead mill treatment was filtered using a metal mesh filter to remove the zirconia beads.

[0518] Next, the lubricating base oil was mixed with the liquid from which the zirconium oxide beads were removed, and pentane was volatilized to prepare an additive composition (A4-1) containing 20% ​​by mass of the metallic nanoparticles (X).

[0519] (Production Example C4-1: Preparation of Grease Composition (C4-1))

[0520] The base grease and the additive composition (A4-1) were mixed so that the content of the metal nanoparticles (X) in the grease composition was 4 mass % based on the total amount of the grease composition, thereby obtaining a grease composition (C4-1).

[0521] <Production Example 4-2: Preparation of Grease Composition (C4-2)>

[0522] (Production Example A4-2: Preparation of Additive Composition (A4-2))

[0523] An additive composition (A4-2) was obtained by the same method as in Production Example A4-1 except that TiN was replaced by WS2 and zirconia beads (1) were replaced by 152 g of zirconia beads (3) (particle size: 0.20 mm).

[0524] (Production Example C4-2: Preparation of Grease Composition (C4-2))

[0525] The additive composition (A4-1) was replaced with the additive composition (A4-2), and a grease composition (C4-2) was obtained in the same manner as in Production Example C4-1.

[0526] <Comparative Production Example 4-1: Preparation of Grease Composition (C'4-1)>

[0527] A mixed solution of powdered TiN and a lubricating base oil was prepared, and the mixed solution was mixed with a base grease so that the content of powdered TiN in the grease composition was 4 mass % based on the total amount of the grease composition, and pentane was volatilized to obtain a grease composition (C'4-1).

[0528] <Comparative Production Example 4-2: Preparation of Grease Composition (C'4-2)>

[0529] A mixed solution of powdered WS2 and a lubricating base oil was prepared, and the mixed solution was mixed with a base grease so that the content of powdered WS2 in the grease composition was 4% by mass based on the total amount of the grease composition, and pentane was volatilized to obtain a grease composition (C'4-2).

[0530] <Comparative Production Example 4-3: Preparation of Grease Composition (C'4-3)>

[0531] A mixed liquid obtained by mixing carbon and a lubricating base oil was prepared, and the mixed liquid was mixed with a base grease so that the carbon content in the grease composition was 4 mass % based on the total amount of the grease composition, and pentane was volatilized to obtain a grease composition (C'4-3).

[0532] <Comparative Production Example 4-4: Preparation of Grease Composition (C'4-4)>

[0533] (Comparative Production Example A'4-4: Preparation of Additive Composition (A'4-4))

[0534] An additive composition (A'4-4) was obtained by the same method as in Production Example A4-1 except that the polymer (Y2) was replaced with the polymer (Y'2).

[0535] (Comparative Production Example C'4-4: Preparation of Grease Composition (C'4-4))

[0536] The additive composition (A4-1) was replaced with the additive composition (A'4-4), and a grease composition (C'4-4) was obtained in the same manner as in Preparation Example C4-1.

[0537] [Examples 4-1 to 4-2, Comparative Examples 4-1 to 4-5]

[0538] The following studies were conducted on each of the grease compositions and base greases prepared in the above-mentioned Production Examples.

[0539] <Evaluation of Volume Resistivity>

[0540] The volume resistivity was measured under the following conditions using a digital ultra-high resistance / micro ammeter (ADCMT5451) and a resistance sample box (ADCMT12707) manufactured by ADC Corporation using a dedicated electrode for 12707.

[0541] Measurement voltage: 40V, sample weight: 0.8g

[0542] <Wear test>

[0543] A high-speed reciprocating friction tester TE77 (manufactured by Phoenix Tribology) was used to introduce a grease composition between a test plate and a test ball. The test ball was moved under the following conditions to conduct the test. The longitudinal and transverse wear scar diameters of the test ball after the test were measured, and the average wear scar diameter was calculated using the following formula.

[0544] Test plate material: SUJ2, shape: length 58mm × width 38mm × thickness 3.9mm

[0545] Test ball material: SUJ2, diameter 10mm

[0546] Grease supply conditions: Grease bath, grease volume 3mL

[0547] Load: 50N (300 seconds)

[0548] Temperature: 100℃

[0549] Amplitude: 10mm

[0550] Frequency: 10Hz

[0551] Average value of wear scar diameter={(longitudinal wear scar diameter)+(lateral wear scar diameter)} / 2. The smaller the wear scar diameter value, the more excellent the wear resistance of the grease composition.

[0552] In addition, the smaller the value of the friction coefficient is, the more excellent the friction characteristics of the grease composition can be said to be.

[0553] The results are shown in Table 6.

[0554] It should be noted that the results of the average particle size measurement when the metal nanoparticles (X) were dispersed in heptane in Preparation Example 4-1, Preparation Example 4-2, and Comparative Preparation Example 4-4 are also recorded in Table 6. The average particle size measurement is the same as in "1. Study on the dispersibility of metal nanoparticles (X)".

[0555] [Table 6]

[0556] Table 6

[0557]

[0558] From Table 6, we can know the following.

[0559] It is found that the grease compositions of Examples 4-1 and 4-2 have high electrical conductivity and excellent friction and wear properties.

[0560] On the other hand, it is found that the grease compositions of Comparative Examples 4-1 to 4-5 have low electrical conductivity and poor friction and wear properties.

[0561] It should be noted that, from the comparison between Example 4-1 and Comparative Example 4-4, it is considered that the grease composition of this example has a low volume resistivity and excellent wear resistance as a result of the high dispersion of the metal-based nanoparticles (X).

Claims

1. A composition, wherein Containing metal nanoparticles (X), polymer (Y) and dispersion medium, The polymer (Y) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group, The metal nanoparticles (X) and the polymer (Y) are dispersed in a dispersion medium, The composition is used as an additive composition for a lubricating oil composition, an additive composition for a grease composition, a lubricating oil composition or a grease composition.

2. The composition according to claim 1, wherein The metal-based nanoparticles (X) include metal-based nanoparticles (X1), wherein the metal-based nanoparticles (X1) are metal nanoparticles formed by one or more metal elements (x1) selected from transition metal elements and metal elements and semi-metal elements from Groups 12 to 15, nanoparticles formed by oxides of the metal element (x1), nanoparticles formed by nitrides of the metal element (x1), nanoparticles formed by sulfides of the metal element (x1), nanoparticles formed by carbides of the metal element (x1), and one or more metal-based nanoparticles formed by borides of the metal element (x1).

3. The composition according to claim 1 or 2, wherein The polymer (Y) is one or more selected from the group consisting of a polymer (Y1) and a polymer (Y2), the polymer (Y1) comprises two or more selected from the group consisting of a constituent unit derived from the following monomer (ya), a constituent unit derived from the following monomer (yb), and a constituent unit derived from the following monomer (yc), and the polymer (Y2) comprises a constituent unit derived from the following monomer (yb) and does not contain a constituent unit derived from the following monomer (ya) and a constituent unit derived from the following monomer (yc), ·Monomer (ya): Olefin having 12 to 30 carbon atoms Monomer (yb): a vinyl monomer having a nitrogen-containing heterocyclic group in which at least one hydrogen atom is substituted by a chain alkyl group having 12 to 30 carbon atoms Monomer (yc): a vinyl monomer having a nitrogen-containing heterocyclic group in which none of the hydrogen atoms is substituted by a linear alkyl group having 12 to 30 carbon atoms.

4. The composition according to claim 3, wherein The polymer (Y1) contains a structural unit derived from the monomer (ya) and a structural unit derived from the following monomer (yc).

5. The composition according to claim 3 or 4, wherein The monomer (ya) contains a linear α-olefin having 12 to 30 carbon atoms.

6. The composition according to any one of claims 1 to 5, wherein The nitrogen-containing heterocyclic group is a monovalent group obtained by removing one hydrogen atom from a pyrrolidone ring.

7. The composition according to any one of claims 1 to 6, wherein The content ratio [(Y) / (X)] of the polymer (Y) to the metal nanoparticles (X) is 0.2 or more in terms of mass ratio.

8. The method for producing a composition according to any one of claims 1 to 7, wherein The method comprises the following steps (1), Step (1): a step of dispersing a precursor of metal nanoparticles (X) in the presence of a polymer (Y) and at least one liquid dispersion medium selected from an organic solvent and a lubricating base oil, The polymer (Y) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group.

9. The composition according to any one of claims 1 to 7, wherein The composition is an additive composition for the lubricating oil composition or an additive composition for the grease composition, The dispersion medium is at least one selected from an organic solvent and a lubricating base oil.

10. The composition according to claim 9 for use as an anti-wear agent.

11. A lubricating oil composition, wherein: Contains metal nanoparticles (X), polymer (Y) and lubricant base oil. The polymer (Y) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group, The metal nanoparticles (X) and the polymer (Y) are dispersed in a lubricating base oil.

12. The lubricating oil composition according to claim 11, wherein The average particle size of the metal nanoparticles (X) is less than 600 nm.

13. A grease composition, wherein: Contains metal nanoparticles (X), polymer (Y) and grease. The polymer (Y) is a vinyl polymer having a chain alkyl group having 10 to 28 carbon atoms and a nitrogen-containing heterocyclic group, The metal nanoparticles (X) and the polymer (Y) are dispersed in the grease.

14. The grease composition according to claim 13, wherein The volume resistivity is less than 1.0×10 13 Ω cm.

15. The grease composition according to claim 14, which is used for preventing electrical corrosion.

Citation Information

Patent Citations

  • Polymeric inorganic nanoparticle compositions, methods for their preparation, and their use as lubricants

    JP2021512188A

  • Polymeric inorganic nanoparticle compositions, methods for their preparation, and their use as lubricants

    JP2021512189A